The effect of approach velocity on centre of mass motion and performance of the maximal instep soccer kick - Augustus, S.; Smith, N.; Hudson, P. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate the influence of approach velocity on centre of mass (CoM) motion and total body angular momentum during the maximal instep soccer kick. Four semi-professional players performed kicks at Self-Selected (SS), Fast and Slow approach speeds and full body motion was captured at 1000Hz. Dependent variables were CoM approach velocity, CoM deceleration impulse, foot velocity, ball velocity and maximum angular momentum about total body CoM. Foot and ball velocities were significantly larger in the Fast compared to Slow condition. Approach speed was strongly correlated to foot and ball velocity, whereas there was no correlation between CoM deceleration impulse and foot and ball velocities. Training soccer players to approach the ball at slightly faster velocities than their perceived optimal speeds may be beneficial for performance.